Ḥukm al-Ḥijāb wa al-Niqāb ʼinda Fuqahāʻ ʼAṣr al-Ḥadīth - Aida Humaira (Al-Zahra : Journal for Islamic and Arabic Studies, 2006)
Women problem is never ending discussion. Hijab and Niqab is an important aspect that becomes Ulama debates. This paper described contemporary Ulama and traditional Ulama perspective of the problem.